Factores de riesgo en relación con neumonía adquirida en la comunidad de la ciudad de Loja - Mosquera Jimbo, Pablo Andrés (2014)
The following research is based on the acquired pneumonia in the community, is a cosmopolitan disease that affects adults with higher incidence, that is why this whose objective research are: Identify the risk factors and their influence in community-acquired pneumonia; Establish independent and individual general factors; and structuring an educational proposal on risk factors. It is descriptive and longitudinal using interviews and direct observation of 60 patients diagnosed with acquired pneumonia in the community or extra-hospital, treated at Services Hospital and Outpatient Regional Hospital "Isidro Ayora" city of Loja, during the period from February to July 2013, with the following results: of the 60 patients diagnosed with NAC 75% are over 65 years old; 55% of patients were female and 45% are male; 95% are of mixed race and 5% are Indian race. The province of Loja had 43.4% of patients diagnosed with NAC, the city of Loja was 41.6%: patients treated in hospital of 93.4% and 6.6% outpatients: the medical history co0mo hypertension with a percentage of 41% and 26% T2DM; unhealthy habits of alcoholism and smoking 46% to 36%. Keywords: NAC Community Acquired Pneumonia.